2009
DOI: 10.4081/jae.2009.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Commercial Optical Sensors for Crop Monitoring Tasks in Precision Viticulture

Abstract: The emergence of precision agriculture technologies and an increasing demand for higher quality grape products has led to a growing interest in Precision Viticulture. Actually, cultural monitoring is the most important application in PV systems: it requires specific technologies able to investigate the cultural conditions. To this aim, typically remote sensing surveys are adopted. These, anyhow, involve technical, economical and organisational barriers hampering a wide diffusion of their application. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Both proximal sensors are normally used to monitor cover crops to manage nitrogen fertilization according to the logic of variable rate application (Govaerts et al, 2007;Sripada et al, 2008). These devices were proposed to monitor crop vigour variations as an alternative to the acquisition of multispectral images (Lamb et al, 2009); in particular, Drissi et al (2009) and Mazzetto et al (2009) suggested the application of the GreenSeeker to monitor vigour variations of Vitis vinifera plants in vineyards. Previous experiences were carried out by the authors in field using a mobile lab equipped with GreenSeeker sensor, in order to evaluate its efficiency in detecting the dynamic diffusion of disease incidence directly in vineyard (Mazzetto et al, 2010(Mazzetto et al, , 2011.…”
Section: Resumen Evaluación De Sensores óPticos Para El Diagnóstico Dmentioning
confidence: 99%
“…Both proximal sensors are normally used to monitor cover crops to manage nitrogen fertilization according to the logic of variable rate application (Govaerts et al, 2007;Sripada et al, 2008). These devices were proposed to monitor crop vigour variations as an alternative to the acquisition of multispectral images (Lamb et al, 2009); in particular, Drissi et al (2009) and Mazzetto et al (2009) suggested the application of the GreenSeeker to monitor vigour variations of Vitis vinifera plants in vineyards. Previous experiences were carried out by the authors in field using a mobile lab equipped with GreenSeeker sensor, in order to evaluate its efficiency in detecting the dynamic diffusion of disease incidence directly in vineyard (Mazzetto et al, 2010(Mazzetto et al, , 2011.…”
Section: Resumen Evaluación De Sensores óPticos Para El Diagnóstico Dmentioning
confidence: 99%
“…The latter, in particular, has been used in vineyard fields to sense canopy reflectance and calculate vegetation indices, which have been further related to canopy porosity (Tardáguila et al, 2008), leaf area index projected onto a vertical plane (VLAI) (Drissi et al, 2009), and pruning weight (Stamatiadis et al, 2006). Mazzeto et al (2009) corroborated the feasibility of calculating standard vegetation indices such as the NDVI with Greenseeker TM in vineyards; nevertheless, these commercial devices are not polyvalent and the information obtained from them has seldom taken part in decision making algorithms of PA applications. Some of them can only be used in bulk crops or do not incorporate GPS receivers, which complicates the sharing of data coming from other sensors with the final goal of explaining variability and casting predictions.…”
Section: Segmentación Automática De Imágenes Digitales Para Estimar Ementioning
confidence: 90%
“…The threshold value applied is 0.60 and it was selected in order to emphasise the small differences in vegetative vigour level within the vineyard. This value has been identified through the examination of values proposed in literature and the frequency analysis of data collected during preliminary tests carried out in greenhouse [Mazzetto 2009]. NDVI maps clearly show differences in vegetation conditions in the two groups of rows.…”
Section: Optical Datamentioning
confidence: 99%
“…Currently, there are several commercial active optical ground sensing devices available: one of the most used devices is the GreenSeeker RT100 (Ntech Industries Inc., Ukiah, USA). Recently the GreenSeeker application in viticulture has been studied to characterise spatial distribution of vine vegetation vigour [Drissi 2009;Mazzetto 2009]. Groundsensing optical sensors were also investigated to detect disease symptoms on wheat and to discriminate between pathological and nutritional stresses [Moshou 2006].…”
Section: Introductionmentioning
confidence: 99%